Pengaruh Kredit Bermasalah dan Tingkat Kecukupan Modal terhadap Kinerja Keuangan pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Oka, I Gede; Mile, Yuldi; Jurana, Jurana (Jurnal Reviu Akuntansi dan Keuangan)
This research aims to test the influence of bad debt as measured by the non-Performing Loan(NPL), and capital adequacy levels as measured by the Capital Adequacy Ratio (CAR) againstthe financial performance as measured by Return on Assets (ROA) at banking company listed onthe Indonesia stock exchange (idx). This research belongs to a causative research. The population in this research is the entire banking company registered in BEI years 2009 to 2011. Whilethe study sample is determined by metodepurposive sampling so that the retrieved samplecompanies. Types of data used are secondary data obtained from www.idx.co.id. Methods ofanalysis used is multiple regression analysis. Based on the results of a multiple regressionanalysis with a level of significance of 5%, then the results of this research concluded:(I) thesimultaneous, Non-Performing Loan and Capital Adequacy Ratio have effect on the financialperformance (ROA) (2) Non Performing Loan has a negative influence and significantly to financial performance (3) Capital Adequacy Ratio significantly affect against the positive financialperformanceKeywords: Bad Debt, The Level Of Capital Adequacy, Financial Performance